Synthesis and characterization some complexes of azo dye of pyrimidyniyl and evaluating their biological activity - Jwad Sahar, Yareeb; Shamran Mohammed, Hasan (Al-Qadisiyah Journal of Pure Science, 2019)
The present study involves fabrication a heterocyclic azo dye: 2-[4-diamino-3-benzaldehyde diazenyl]pyrimidine (L). The dye was synthesized by reacting 2-aminopyrimidine with 4-diaminobenzaldehyde (in situ). The complexes of ([Ag(L)(H2O)]NO3, [Cd(L)2]Cl2 and [Hg(L)2]Cl2) dyes were prepared and characterized by elemental analysis; mass spectra, molar conductivity and spectroscopies of infrared and UV-Vis. The L dye ligand is tridentate. The Cd(II) and Hg(II) are octahedral with mole ratio Metal:Ligand equal to 1:2 while Ag(I) complex is tetrahedral with mole ratio Metal:Ligand equal to 1:1. The molar conductivity indicates that Ag(I) complex is electrolyte (1:1) and Cd(II) and (II) are electrolytes with ratio 2:1. The synthesized ligand (L) and its complexes showed interest biological activity against E-coli and Staph-aureus bacteria and Aspergillus Niger and Pinicillium.sp fungi. The anti-activity of [Ag(L)(H2O)]NO3 complex against MCF-7 cell line and its cytotoxicity against WRL cell line were interesting in vitro.